SEJARAH RUMAH ADAT KARO DI DESA DOKAN KECAMATAN MEREK KABUPATEN KARO - Hafnita Sari Dewi Lubis; Pristi Suhendro Lukitoyo; Dandi Arihta Sitepu; Prisai Mono Putra Tarigan; Fitria Rizki Aulia (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
Abstract The purpose of this research is to know the history of the establishment of the Karo traditional house in Dokan village, Brand district. Another goal is to see the legacy of the oldest traditional building in the Karo community in Dokan village, and to see how the condition of the building is now. Here the research also finds out whether there is still a role for the government and the community in the preservation of the Karo traditional house which is located in the village of Dokan. In obtaining the data, the researcher used field research and library research, namely by looking directly at the physical condition of the Karo traditional house located in the Dokan cultural village. It turns out that the Karo traditional house in Dokan village is still occupied by several families, one of which is Mr. Sitepu's family, they are also still preserving the Karo cultural musical instruments and even making them themselves. This traditional house in Dokan village is called the traditional house (Siwaluh Jabu) Eight Families which when we went directly to the location it was only occupied by four families. The results of our research are knowing the history of the Karo traditional house located in Dokan village and the Karo cooking utensils which are still used today. From this research, we also know how the government's role in preserving the Karo traditional house is located in the Dokan cultural village.